Multiple factors contribute to flight behaviors during fear conditioning - Furuyama, Takafumi; Imayoshi, Ayana; Iyobe, Toyo; Ono, Munenori; Ishikawa, Tatsuya; Ozaki, Noriyuki; Kato, Nobuo; Yamamoto, Ryo (Scientific reports, 2023)
Shifting defensive mode from one to another by the imminence of threat is crucial for survival. The transition of defensive mode from freezing to flight is observed during the modified fear conditioning, however, the flight during fear conditioning is not well characterized. To characterize the flight behaviors during the fear conditioning, we conducted experiments in male mice focusing on the influence of the context, the intensity of the unconditioned stimulus and conditioned stimulus (CS), the schedule of conditioning, and the state of the subject. Flight behaviors triggered by salient CS showed characteristics of fear-potentiated defensive behaviors depending on the conditioned context, while repetitive conditioning enhanced the expression of the flight and developed an association between the CS and the flight. The salient auditory stimulus was the primary factor to trigger flight behaviors. Also, the spaced conditioning increased the expression of flight behaviors. Taken together, the flight behavior during fear conditioning is not a simple conditioned response nor simple fear-potentiated behavior, but a complicated mixture of multiple components of defensive behaviors. The transition of defensive mode could be induced by the integration of multiple innate and learned components of fear or anxiety.